Peran Kelembagaan Petani Dalam Pengembangan Usahatani Kopi Arabika (Coffea arabica) Di Desa Kendenan Kecamatan Baraka Kabupaten Enrekang - Ummul Khaerah; Nurdin Nurdin; Akbar Akbar (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
The research aims to determine the existing institutions and the institutional role of farmers in the development of Arabica coffee farming. Determination of the sample using purposive sampling technique. The samples obtained were 14 people. The data analysis used is a qualitative data analysis method. The results showed that there were 3 farmer institutions including: Farmer Groups, Association of Farmer Groups (Gapoktan), Women Farmer Groups (KWT). The institutional role of farmers is the role of farmer groups, namely as a learning unit, as a cooperation unit, and as a production unit. Gapoktan's role is to provide capital and collectively market the results. The role of farmer women's groups, namely, as a unit of cooperation, as a learning unit and as a production unit.Â